Los patios de las escuelas primarias como espacios del aprendizaje de la ciudadanía mexicana - Dalila Chine-Lehmann (Les Cahiers ALHIM)
In a world in which it is claiming the emergence of new socio-political movements, the state tries to strengthen its national symbols through various instruments such as schools. Our article will be based on the role of civic ceremonies in Mexican elementary schools today. To direct the reading of a collective memory that integrates all children in society, the Mexican government uses schools and patriotic ceremonies to strengthen the sense of national identity. By this "learning by body" (Bourdieu, 1980), the student must respect the various official symbols (singing the hymn, honoring the flag) and internalize the respect and love of country. To understand the role of these civic ceremonies, we will use an ethnographic research carried out in various primary schools in Mexico (Mexico City, San Luis Potosí, Puebla) in which, each week, official symbols are celebrated. These celebrations take place in closed spaces (those in the school yard) and also in official ones (near public monuments). What are the purposes and the limits of these ceremonies? We will see that the school is actually transmitting a cult and values according to the national project. It tries to set a symbolic logic that retreat student into their own culture in order to avoid contradicting the role of a protective state.